Pandangan ulama terhadap karya dan ketokohan Muhammad bin Ishaq - Wan Kamal Mujani (Penerbit Universiti Kebangsaan Malaysia, 1999)

(untitled)
Muhammad bin Ishaq or Ibn Ishaq is one of the most distinguished and prominent historian in the beginning of the Islamic historiography. He was the great pioneer in the systematic methodology of historiography. He tremendously brought the writings of Sirah and Maghazi to the highest position. His writings was at the meantime regarded as the primary source for the later historians. He was very learned and possessed the most outstanding ability especially in compiling information from various sources and his ability in arranging the compiled data. Thus these invaluable skills earned him as top historian compared to those of the earlier historians. His book on Kitab al-Mubtada’ wa al-Mabcath wa al-Maghazi mirrors his comprehensive understanding pertaining to the Sirah and Maghazi compared to the earlier writers and those of the same period. This was due to the fact that the particular book consisted of the history of the prophet in the preface and of the history of the companions which were beautifully arranged according to standard methodology of writing. Even though Ibn Ishaq received great criticisms from some of the Muhaddithin, his contributions and role played in developing the field of Islamic historiography were considered as one of the most undeniable fact when he obtained recognition from Muhammad bin Muslim al-Zuhri and Muhammad bin Idris al-Shafice. Since most of the hadith scholars were in favour of him, those allegations which question his authority need to be re-assessed